Marketing Stadiums as Event Venues: Modified Balanced Scorecard (mBSC) Evaluation of Minor League Baseball Websites as an eMarketing Tool - Charles Parrish; Seungwon "Shawn" Lee; Ji-Ho Kim (Journal of Applied Sports Management, 2014)
Maximizing and gaining access to stadium related revenue streams, including non-game day social and corporate event rentals, is a critical factor for the financial viability of professional sports teams. Minor League Baseball (MiLB) teams and Independent baseball league (Indy) teams are no exception and franchise owners strive to maximize ancillary business opportunities, including stadium usage year-round. Currently, teams are marketing their venues through various mediums, including their websites. Considering the implications of eMarketing on MiLB and Indy teams’ ability to target and solicit social and corporate event customers it is critical to evaluate current eMarketing efforts. This study employs the Modified Balanced Scorecard (mBSC) approach to website evaluation and aims to a) evaluate the contents and design of minor league (MiLB and Indy) baseball teams’ websites as a marketing tool for their stadiums and b) to identify trends of minor league baseball stadium use as social and corporate event venues. Research findings provide researchers and industry professionals with empirical evidence of the current positioning of minor league baseball stadiums as social and corporate event venues. The authors also discuss how teams can improve their eMarketing strategy to better engage social and corporate event clients.
Keywords: stadiums; event/meeting venue; eMarketing; modified balanced score card (mBSC); Minor League Baseball